Mencari Tuhan di Tengah Tantangan: Refleksi Zefanya 2:1-3 - Tickos Elia Siahaan; Landong Sihombing; Veronika Tumangger; Herdiana Boru Hombing (Pusat Riset dan Inovasi Nasional, 2025)
This interpretation discusses Zephaniah 2:1-3 with the aim of revealing the main message of the passage and how its meaning can be applied to contemporary life. This verse contains God's invitation to His people to immediately gather and repent before His wrath comes. The method used in this interpretation is a historical and contextual approach, by tracing the background of Zephaniah's time, the meaning of key words in the text, and their relationship to modern life. The results of the interpretation show that Zephaniah invites the people to seek God, live a life of justice, and be humble. This is not only a call for the Israelites at that time, but also a warning for modern humans who live in a situation of moral crisis, disaster, and social chaos. This verse invites everyone not to delay repentance, live righteously before God, and maintain good relations with others. The message is very relevant to modern life which often forgets spiritual values ​​and social justice.